A GENEALOGICAL RECONSTRUCTION OF LUBUKUSU, LUMASABA AND LUGISU - Lwangale, David Wafula (IJRDO-Journal of Applied Science, 2015)
A genealogical study is aimed at establishing a historical relationship among languages. Thestudy at hand focused on the genealogical relationship that runs across Lubukusu, Lugisu,and Lumasaba. The presumption that classification of Luluhyia language was incompleteprovided the basis of the study and a comparative reconstruction of a proto-language forLubukusu, Lumasaba and Lugisu was done. Random and stratified sampling procedurebecame very instrumental in sample selection of informants and word forms. Data collectionwas done through oral interviews as well as use of questionnaires. Data analysis andinterpretation was by use of descriptive statistics specifically proportion percentages andmeans. The research confirmed its objectives to be valid, that is, established that Lugisu andLumasaba are dialects of Luluhyia language and successful attempt of “protomundu”reconstruction was done. Thus, the claim that Lubukusu, Lugisu, and Lumasaba are ofcommon descent and that they are all dialects of Luluhyia language is true.